Neural network based switching control of AC-AC converter with DC-AC inverter for voltage sags, harmonics and EMI reduction using hybrid filter topology - Gulez, Kayhan (ELSEVIER, 2008)
A neural network based AC-AC voltage restorer is designed for voltage sags and PWM type active power filter with compound trap passive filter as a new hybrid filter are simultaneously used for voltage harmonics compensation and electromagnetic interference (EMI) reduction. First objective is to apply the neural network based switching control technique for the AC-AC voltage restorer to reduce time delays during the switching conditions and switching losses. The aim of the IGBTs used in the AC-AC voltage restorer is to test and to find the best switching frequency-power combination in the steps of the simulation. Thus, the proposed AC-AC voltage restorer has important advantages such as fast switching response, simplicity and more intelligent structure, better output waveform. The transient condition of the AC-AC voltage restorer is improved via the neural network based control technique. The second objective is the proposed strategy for elimination of voltage harmonics using PWM type DC-AC inverter part of the system as an active power filter. The last objective of the system is EMI reduction with using hybrid filter and voltage restorer together. Three problems which are voltage sags, harmonics and EMI are solved with the proposed system simultaneously. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: neural networks; switching control; AC-AC converter; voltage sag; voltage harmonics; EMI reduction; hybrid filter; Computer Science